Eco-Friendly Synthesis of Silver Nano Particles Using Carica papaya Leaf Extract - Jackson, Tenderwealth Clement; Uwah, Timma Oto-Obong; Agboke, Akeem Ayodeji; Udo, Blessing Edidiong; Udofa, Edidiong Michael (Scientific Research, 2018)
Silver nanoparticles were synthesized using eco-friendly method with extract of Carica papaya as reducing and stabilizing agent. The silver precursor used was silver nitrate solution. A visible colour change from colourless to reddish brown confirmed the formation of the nanoparticles and the UV-Vis spectroscopy showed surface plasmon resonance of 435 nm for the silver nanoparticle. The mean particle size was 250 nm while the polydispersity index was 0.22. The antimicrobial activity of the synthesized nanoparticles was studied against Pseudomonas aeruginosa, Escherichia coli, Bacillus subtilis and Staphylococcus aureus. The silver nanoparticles biosynthesized showed satisfactory antimicrobial activity against the test isolates. Antimicrobial property of the nanoparticles was similar (P > 0.05). Generally, MIC values of the samples against the microorganisms tested ranged from 25 - 100 mg/ml. Pseudomonas aeruginosa was most sensitive while Staphylococcus aureus and Bacillus subtilis were least sensitive to the silver nanoparticles.
Keywords: Silver Nanoparticles; Eco-Friendly Method; Characterisation; Antimicrobial